Gigantic Current Control of Coercive Field and Magnetic Memory Based on Nanometer‐Thin Ferromagnetic van der Waals Fe3GeTe2. Issue 4 (6th December 2020) - Zhang, Kaixuan; Han, Seungyun; Lee, Youjin; Coak, Matthew J.; Kim, Junghyun; Hwang, Inho; Son, Suhan; Shin, Jeacheol; Lim, Mijin; Jo, Daegeun; Kim, Kyoo; Kim, Dohun; et al.
Abstract: Controlling magnetic states by a small current is essential for the next‐generation of energy‐efficient spintronic devices. However, it invariably requires considerable energy to change a magnetic ground state of intrinsically quantum nature governed by fundamental Hamiltonian, once stabilized below a phase‐transition temperature. Here, it is reported that, surprisingly, an in‐plane current can tune the magnetic state of the nanometer‐thin van der Waals ferromagnet Fe3 GeTe2 from a hard magnetic state to a soft magnetic state. It is a direct demonstration of the current‐induced substantial reduction of the coercive field. This surprising finding is possible because the in‐plane current produces a highly unusual type of gigantic spin–orbit torque for Fe3 GeTe2 . In addition, a working model of a new nonvolatile magnetic memory based on the principle of the discovery in Fe3 GeTe2, controlled by a tiny current, is further demonstrated. The findings open up a new window of exciting opportunities for magnetic van der Waals materials with potentially huge impact on the future development of spintronic and magnetic memory. Abstract : Substantial coercivity reduction by the current, larger at least by two orders of magnitude than those in previous reports, is found in the van der Waals ferromagnet Fe3 GeTe2 . It is theoretically shown to arise from an unusual type of gigantic spin–orbit torque, which itself is directly related to its special symmetries, large Berry curvature, and band topology. A working model of a new robust nonvolatile magnetic memory based on Fe3 GeTe2, controlled by a much smaller current, is also produced.